Glucocorticoids Elevate Pseudomonas aeruginosa Binding to Airway Epithelium by Upregulating Syndecan-1 Expression - Liu, Dong; Zeng, Ying-Ying; Shi, Meng-Meng; Qu, Jie-Ming (Frontiers in Microbiology, 2021)
Glucocorticoids are commonly used for the treatment of asthma and chronic obstructive pulmonary disease (COPD). Inhaled corticosteroids are associated with a significantly increased risk of pneumonia. Syndecan-1 (SDC1) located in the cell membrane of airway epithelial cell is the crucial molecule mediating infections by P. aeruginosa (PA). In the present study, we found that SDC1 expression was upregulated and the adhesion of PA to human bronchial epithelial (HBE) cells increased to 125 and 138%, respectively, after stimulation by dexamethasone or budesonide. The HBE cells knocking down SDC1 showed lower affinity to PA compared with control. CCAAT-enhancer-binding protein β (C/EBP β) and its phosphorylated form participated in the regulation of glucocorticoid to SDC1 for interfering C/EBP β or inhibiting phosphorylation of C/EBP β by LiCl and BIO, which are inhibitors of glycogen synthase kinase 3β (GSK-3β), and could prevent glucocorticoids from upregulating SDC1 expression. One should be cautious in administering glucocorticoids in chronic lung disease because of their property of increasing the expression of SDC1 and PA binding to the airway epithelium.